Hypertension Detector Based on Internet of Things - Suryaatmaja, Oktavia Dewi; Koesmarijanto, Koesmarijanto; Marya, Dianthy (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Hypertension, a leading global non-communicable disease and a major risk factor for cardiovascular mortality, requires continuous monitoring due to its often asymptomatic nature. This research aims to design and implement an Internet of Things (IoT)-based system for detecting and managing hypertension. The system comprises a prototype detector device for measuring blood pressure and a complementary mobile application for data communication. The development follows the Research and Development (R&D) methodology. The application facilitates remote patient monitoring by connecting doctors and patients, featuring data logging, chat, call, and video call functionalities for timely medical intervention. The prototype blood pressure detector was validated through ten tests on different subjects, comparing its systolic and diastolic readings against a standard sphygmomanometer. Results indicate an average error of 16.9% for systolic pressure and 17.2% for diastolic pressure, corresponding to accuracy rates of 83% and 82.8%, respectively. The observed variations in error are attributed to differing patient physiological conditions during measurement. The study concludes that the developed IoT-based system offers a viable solution for remote hypertension monitoring, enabling proactive healthcare management by bridging patients and doctors through integrated hardware and software.